Updated Recommendations for MRI of the Breast (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The managing board of the Breast Imaging Working Group of the German Radiological Society revised the recommendations regarding technique, methods, indications, evaluation, and documentation of MR mammography from the year 2005 1 and adapted them to the improved technical options and the latest scientific knowledge. In relation to technical imaging parameters, these recommendations describe the minimum requirements for acquiring high-quality MRI images of the breast. The recommendations are a general guide to be adjusted by the examiner as needed to suit the individual situation.Citation Format:• Breast Imaging Working Group of the German Radiological Society. Updated Recommendations for MRI of the Breast. Fortschr Röntgenstr 2014; 186: 482 – 483
Keywords: breast diseases; MR imaging; breast cancer